2023
DOI: 10.1038/s41380-023-02005-2
|View full text |Cite
|
Sign up to set email alerts
|

The molecular pathology of schizophrenia: an overview of existing knowledge and new directions for future research

Abstract: Despite enormous efforts employing various approaches, the molecular pathology in the schizophrenia brain remains elusive. On the other hand, the knowledge of the association between the disease risk and changes in the DNA sequences, in other words, our understanding of the genetic pathology of schizophrenia, has dramatically improved over the past two decades. As the consequence, now we can explain more than 20% of the liability to schizophrenia by considering all analyzable common genetic variants including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 145 publications
1
6
0
Order By: Relevance
“…In addition to NFRKB, SETD1A (SET domain containing 1A) was foun to potentially regulate the second largest group of DETs identified for blood Thmem ce (Figure 2d). As member of the SET1/MLL family methyltransferases, SETD1A was d scribed as influencing chromatin conformation by modulating the methylation of histon H3 at lysine 4 (H3K4me3), resulting in transcriptional activation of the affected genes [51 Interestingly, it was reported that mutations in SETD1A substantially increase the risk f the development of schizophrenia [51,52].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to NFRKB, SETD1A (SET domain containing 1A) was foun to potentially regulate the second largest group of DETs identified for blood Thmem ce (Figure 2d). As member of the SET1/MLL family methyltransferases, SETD1A was d scribed as influencing chromatin conformation by modulating the methylation of histon H3 at lysine 4 (H3K4me3), resulting in transcriptional activation of the affected genes [51 Interestingly, it was reported that mutations in SETD1A substantially increase the risk f the development of schizophrenia [51,52].…”
Section: Resultsmentioning
confidence: 99%
“…The ability to generate iPSCs from well-characterized schizophrenia patients and healthy subjects enables us to generate neuronal cells that have the same genetic background as the subjects and interrogate biological differences that result from the collective effect of the complex genetic backgrounds [58][59][60][61][62]. There is convergent data, including from iPSCbased studies, that implicate deficits in synaptic biology in the etiopathogenesis of schizophrenia [63][64][65]. Schizophrenia is typically diagnosed in adolescence or early adulthood [66].…”
Section: Discussionmentioning
confidence: 99%
“…In identifying potential therapeutics, we noticed that the KMT2C target genes detected by ChIP-seq of the adult brain (Fig. 2i-k and Supplementary Table 4a) strikingly overlap with the targets of SETD1A [13] (Supplementary Table 6), another histone methyltransferase catalytic unit known as an established risk gene for schizophrenia and other neurodevelopmental disorders [12,14,15], in the brain (Fig. 5a, P = 2.83 × 10 −86 , hypergeometric test).…”
Section: Colocalization Of Kmt2c With H3k4me3 and Downregulated Degs ...mentioning
confidence: 99%
“…De novo LOF variants of KMT2C were also identified in patients clinically diagnosed with Kleefstra syndrome, whose characteristic symptoms include autistic-like features [11]. Besides, other members of the H3K4 methylation regulators were reported to be associated with other neurodevelopmental syndromes with ASD symptoms and neuropsychiatric disorders such as schizophrenia [12][13][14][15]. Therefore, KMT2C haploinsufficiency is an established causative risk factor of ASD and NDD with autistic symptoms, and it has been indicated that H3K4 methylation plays an important role in brain development and cognitive functions [16]; however, little is known about how it causes neurodevelopmental deficits and how these conditions can be treated.…”
Section: Introductionmentioning
confidence: 99%